Trump’s Policy of Increasing Import Tax Rates: Reception Analysis - Muhammad Ruslan Ramli; Salman; Ballian Siregar; Faqih Imtiyaaz Abdillahsyah (International Journal of Advanced Multidisciplinary, 2026)
This study discusses the reception of lecturers regarding the latest policy news from the President of the United States (US) Donald Trump which was published in the national media in April 2025. Trump issued a policy of increasing import tax rates for foreign countries importing goods into the US. Even though the global situation is not conducive with a series of conflicts between countries, Trump insisted on raising it. The problem is how lecturers accept Trump's  policy of increasing import tax rates. This research aims to explain their reception of Trump’s new trade tax policy. This research uses a qualitative-descriptive method through an analytical study of Stuart Hall's reception with three elements; domination, negotiation, and opposition. As the subject of the study, interviews were conducted with informants consisting of lecturers in Jakarta. The results of this study show that most private lecturers in Jakarta are in opposition to Trump's economic policies rather than negotiation and domination. The significance of this research is that there is a spirit of nationalism for every citizen.